USING THE TECHNIQUE OF QUALITY FUNCTION DISSEMINATION (QFD) IN CONTROLLING COSTS AND IMPLEMENTING THE DIFFERENTIATION STRATEGY (AN APPLIED STUDY IN THE UR STATE COMPANY FOR ENGINEERING INDUSTRIES) - Malath Abdul Jabbar Abbas (Scholar Express Journals, 2022)
The research aims to apply one of the strategic cost management techniques, which is the technique of Quality Function Dissemination (QFD) in the Ur State Company for Engineering Industries on the electrical outlet product to determine customer requirements, control costs and implement the differentiation strategy. Responding to the customer's voice, taking into account the competition of economic units to achieve cost reduction, maximum customer satisfaction and the highest quality. The research found a weak interest in cost accounting techniques in general and the dissemination of the quality function in particular, which is reflected in the weakness of the economic unit's ability to develop the product and reduce costs as well as the difficulty in responding to the customer's voice and consequently the lack of control over costs well as well as the failure to implement the differentiation strategy as required .
Keywords: Quality; Function; Dissemination; requirements